Twenty years of lesson learning: how does the RET genetic screening test impact the clinical management of medullary thyroid cancer?. (29th December 2014) - Romei, Cristina; Tacito, Alessia; Molinaro, Eleonora; Agate, Laura; Bottici, Valeria; Viola, David; Matrone, Antonio; Biagini, Agnese; Casella, Francesca; Ciampi, Raffaele; Materazzi, Gabriele; Miccoli, Paolo; et al.
Summary Objective Medullary thyroid carcinoma (MTC) is a rare disease that can be inherited or sporadic; its pathogenesis is related to activating mutations in the RET gene. Design This study describes our 20‐year experience regarding RET genetic screening in MTC. Patients and methods We performed RET genetic screening in 1556 subjects, 1007 with an apparently sporadic MTC, 95 with a familial form and 454 relatives of RET‐positive patients with MTC. Results A germline RET mutation was found in 68 of 1007 (6·7%) patients with sporadic MTC, while 939 patients with MTC were negative for germline RET mutations. We then identified a total of 137 gene carriers (GC). These subjects initiated a clinical evaluation for the diagnosis of MEN 2. A total of 139 MEN 2 families have been followed: 94 FMTC, 33 MEN 2A and 12 MEN 2B. Thirty‐three different germline RET mutations were identified. Codon 804 was the most frequently altered codon particularly in FMTC (32/94, 34%), while codon 634 was the most frequently altered codon in MEN 2A (31/33, 94%); MEN 2B cases were exclusively associated with an M918T mutation at exon 16. Conclusions Our 20‐year study demonstrated that RET genetic screening is highly specific and sensitive, and it allows the reclassification as hereditary of apparently sporadic cases and the identification of GC who require an adequate follow‐up. We confirmed that FMTC is the most prevalent MEN 2 syndrome and that it is strongly correlated with noncysteine RET mutations. According to these findings, a new paradigm of follow‐up of hereditary MTC cases might be considered in the next future.